ANALISIS EFISIENSI BELANJA DAERAH DI KABUPATEN BLITAR JAWA TIMUR TERHADAP KESEJAHTERAAN MASYARAKAT (Studi Kasus pada Bidang Pendidikan, Kesehatan dan Infrastruktur) - Hidayati, Risqi Noor Hidayati; lo, Susi (Jurnal Ilmiah Mahasiswa FEB, 2013)
Spending efficiency is an important issue in the public sector policy, expenditure which efficient is believed can encourage an increase in the welfare. The purpose of this study is to analyze the efficiency of public spending in Blitar Regency to the welfare of society,  especially education, health and infrastructure  spending. This study uses the data on period 2004-2012 and uses Data Envelopment Analysis and Linear Regression. Input variables used are education, health and  infrastructure spending. Output variables for education using the number of schools, number of teachers and number of students,  for health use a number of puskesmas (health centers), the number of health workers and number of immunization and for infrastructure use good road length and exstensive water service. And to see the effect efficiency of  the regional spending on the welfare of society is to use the human development index (HDI).  Based on calculations by the DEA found that the efficiency score  on average in the nine year have not been efficient. However, education, health and infrastructur have a different effect on the welfare of the society through the human development index. The results showed that the efficiency in education  and health  are significant and  negative  effect on the HDI. While,  the efficiency of the infrastructure are not significant and negative effect on the HDIKeyword : Efficiency, public spending, HDI, data envelopment analysis, linear regression